2011
DOI: 10.1002/pen.22063
|View full text |Cite
|
Sign up to set email alerts
|

Moisture absorption behavior and its impact on the mechanical properties of cellulose whiskers‐based polyvinylacetate nanocomposites

Abstract: Cellulose nanowhisker (CNW) reinforced polyvinyl acetate (PVAc) nanocomposites were prepared by meltextrusion using a master batch process. Microscopy images showed no visible aggregation of whiskers in the matrix. The influence of CNWs and moisture absorption on the mechanical behavior of the nanocomposites was studied. The water sorption studies indicated low water uptake (<10 wt%) for all the materials. However, higher moisture uptake was obtained in the nanocomposites compared to the matrix though the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
(41 reference statements)
1
28
0
1
Order By: Relevance
“…It is a general observation that the diffusion pathway is increased by tortuosity effect generating a barrier effect in polymer film which causes a change in the diffusion of small molecules and, hence, in the permeability [8,[11][12][13]. To date, and according to our current knowledge, few works dedicated to transport properties against water, organic solvents, gases for cellulose nanowhisker reinforced biobased materials are reported [2,14,[15][16][17][18][19][20][21], considering the rising interest in both academia and industry since 15 years. Generally, barrier properties obtained when nanofillers are dispersed within a polymer matrix are dependent on the free volume in material, the polymer chain segment mobility, size of diffusing molecules as well as on the dispersion level, the orientation, the amount of dispersed nanoparticles, the formation of dense cellulose network, the interfacial compatibility between nanocomposite elements, or presence of additional additives, etc.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is a general observation that the diffusion pathway is increased by tortuosity effect generating a barrier effect in polymer film which causes a change in the diffusion of small molecules and, hence, in the permeability [8,[11][12][13]. To date, and according to our current knowledge, few works dedicated to transport properties against water, organic solvents, gases for cellulose nanowhisker reinforced biobased materials are reported [2,14,[15][16][17][18][19][20][21], considering the rising interest in both academia and industry since 15 years. Generally, barrier properties obtained when nanofillers are dispersed within a polymer matrix are dependent on the free volume in material, the polymer chain segment mobility, size of diffusing molecules as well as on the dispersion level, the orientation, the amount of dispersed nanoparticles, the formation of dense cellulose network, the interfacial compatibility between nanocomposite elements, or presence of additional additives, etc.…”
Section: Introductionmentioning
confidence: 91%
“…Some authors mentioned that the water vapor barrier properties are found to be increased upon the nanofiller loading and its improved dispersion for cellulose whiskers/ plasticized-carboxymethyl cellulose films [14], surface-carboxylated whiskers/poly(vinyl alcohol) films [2], modified microcrystalline cellulose/plasticized-starch films [16], for instance. A higher water uptake is reported at high water activity (a w ¼ 0.98) for cellulose whiskers/polyvinylacetate nanocomposites [19] Contents lists available at SciVerse ScienceDirect compared with pure matrix and attributed to preferential diffusion pathways with water-rich domains formed at the nanofiller-matrix interfaces. This observation was consistent with previous results on sisal whiskers/polyvinylacetate films [22].…”
Section: Introductionmentioning
confidence: 96%
“…Cellulose nanomaterials such as cellulose nanocrystals (CNC) are often added to the PLA matrix to overcome few of its drawbacks . For instance, well‐dispersed nanocrystals can improve PLA's mechanical properties by improving stress transfer from the matrix to the CNCs .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, well‐dispersed nanocrystals can improve PLA's mechanical properties by improving stress transfer from the matrix to the CNCs . Additionally, CNCs can act as nucleating agents to increase PLA's crystallinity . Increased crystallinity is known to improve the barrier properties of materials because of the increase in packing efficiency of polymer chains, leading to a decrease in free volume .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation